Challenges of State Administrative Court Decisions Implementation: Analysis of Challenges to Execution of State Administrative Court Decisions - Yogo Pamungkas; Amriyati Amriyati; Andari Yurikosari; Richi J Candra (Eduvest - Journal of Universal Studies, 2023)
The problem posed in this study is what are the factors causing the obstruction of the implementation of the PTUN decision? second, what is the solution to the obstruction of the implementation of the PTUN decision?  The purpose of the study is to determine the factors causing the obstruction of the implementation of the PTUN decision and the formulation of solutions for the obstruction of the implementation of the PTUN decision. This study uses doctrinal study methods.  emphasizes the use of secondary data from primary legal materials, especially on regulations related to material and formal aspects of State Administrative Justice, secondary legal materials in the form of reference books and research relevant to the theme of study. Especially for reference books and research will be expanded with historical and social themes to see the social factors that influence the formation of law. Third, tertiary law materials as data discovery tools. The results of this study found that obstacles to the implementation of PTUN decisions are procedural laws that have not been able to provide guarantees about the mechanism for implementing decisions and decisions that do not consider aspects of the state administrative law ecosystem and administrative political ecosystem. In the event that there is a request to issue a decision or take action or revise the decision by issuing a new decision, an ex nunc assessment and the implementing agency of the PTUN decision are required.